Les séries de science-fiction au croisement d’un genre fictionnel et d’une forme narrative audiovisuelle - Florent Favard; Hélène Machinal (ReS Futurae)
Present on television since its beginnings, science fiction became more visible with each passing decade, benefitting, like other televisual genres, from the increase of the annual production of the televised series, which goes on surpassing each of its « peaks ». The prevalence of the serial form in recent years encourages us to consider the genre of science fiction in the light of television seriality, by placing these two elements within a critical dialectic to explore the dynamics between a narrative form and a fictional genre, and the relationship of mutual benefit that is woven between these two objects of study, within a transmedia context. It will thus be a question of answering two reciprocal questions: what does the genre of SF bring to the television seriality? What does the television seriality bring to the SF genre?